2009
DOI: 10.1007/s00198-009-0993-z
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-dependent changes in three-dimensional microstructure of cortical and trabecular bone at the human femoral neck

Abstract: Our findings indicate that Ct.Th and BV/TV decreased, and Ca.V/TV and Ca.Dm increased in femoral neck with age for both women and men. The most obvious age-related change is the increase of Ca.V/TV. The decrease of BV/TV with age is more noticeable than that of Ct.Th. This is the first study that has provided both cortical and trabecular microstructural data simultaneously in a Japanese sample. These data may help us to gain more insight into the potential mechanism of osteoporotic femoral neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
123
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 56 publications
15
123
3
1
Order By: Relevance
“…that most humerus fractures sustained above the age of 50 years were associated with minimal trauma (60.2%), with the incidence being higher in women than in men, and localization at the proximal humerus accounting for some 85% of the fractures. We observed a significant and negative relationship between the Ct.Th of the humerus and age, consistent with age-induced bone loss, (27)(28)(29)(30) indicating that our population was representative of elderly patients with humeral fractures. Shaft fractures accounted for 10% of low-energy humeral fractures, and occurred more frequently in women than in men.…”
Section: Discussionsupporting
confidence: 65%
“…that most humerus fractures sustained above the age of 50 years were associated with minimal trauma (60.2%), with the incidence being higher in women than in men, and localization at the proximal humerus accounting for some 85% of the fractures. We observed a significant and negative relationship between the Ct.Th of the humerus and age, consistent with age-induced bone loss, (27)(28)(29)(30) indicating that our population was representative of elderly patients with humeral fractures. Shaft fractures accounted for 10% of low-energy humeral fractures, and occurred more frequently in women than in men.…”
Section: Discussionsupporting
confidence: 65%
“…Our findings at the tibia are consistent with results of a recent mCT study of human femoral neck cadavers that indicated the relationship with age was similar in men and women for Tb.N, Tb.Th, and Tb.Sp. (45) Thus patterns of trabecular bone loss may vary with skeletal site. Our regression analyses suggest that BV/TV remains relatively constant at the distal radius until midlife and declines thereafter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods for filtering and measuring image features have been described before [21,[23][24][25][26][27][28][29][30][31][32]. Similar image features are current in studies on osteoporosis and bone structure [33][34][35][36][37][38][39].…”
Section: Image Processingmentioning
confidence: 99%